CUSTOMER ENGAGEMENT AND WILLINGNESS TO PAY: ADVOCACY MEDIATION AMONG COSMETICS USERS - Apreyviesca Shallom Euodia Buana; Endah Wartiningsih; Imas Chandra Pratiwi; Nidia Sofa; Mawarta Onida (Jurnal Manajemen dan Bisnis Performa, 2026)
This study aims to analyse the effect of customer engagement on willingness to pay, with customer advocacy acting as a mediating variable among users of Guèle cosmetic products in Jakarta. The study adopts a quantitative research approach and utilises Partial Least Squares–Structural Equation Modelling (PLS-SEM) to examine the proposed relationships. Data were collected from 226 respondents through a purposive sampling technique, targeting consumers who have experience using Guèle products. The findings indicate that customer engagement has a significant positive effect on both customer advocacy and willingness to pay. In addition, customer advocacy is found to have a significant positive influence on willingness to pay, confirming its strategic role in shaping consumer value perceptions. The mediation analysis demonstrates that customer advocacy significantly mediates the relationship between customer engagement and willingness to pay, suggesting that highly engaged customers are more willing to pay a premium when they actively advocate for the brand. Overall, all proposed hypotheses are statistically supported. The results highlight the importance of fostering strong engagement and advocacy-driven relationships with consumers in the highly competitive cosmetic industry. This study provides practical insights for cosmetic brands in designing marketing strategies that emphasise interactive engagement and advocacy initiatives to enhance perceived product value. Furthermore, the study offers directions for future research by encouraging the exploration of additional mediating or moderating variables and broader consumer segments.